Transformasi Layanan Pariwisata melalui Aplikasi Layanan Penyedia Tour guide Berbasis Android - Tandean, Yoga; Yulianingsih, Evi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Tourism is a strategic sector for the Indonesian government to increase domestic and regional income and create jobs. With the development of digital technology, transformation in the tourism industry is crucial to strengthen global competitiveness. This study focuses on the development of an Android-based tour guide service application as a solution to transform tourism services in Indonesia. Currently, the tour guide system in Indonesia is still manual and not standardized, which raises concerns about the quality and security of the service. This application aims to provide a list of licensed tour guides, allow the selection of tour packages according to preferences, and increase transparency through the rating feature. The Extreme Programming (XP) method is used in the development of this system to be responsive to changes in user needs. This research is expected to facilitate the search and rental of tour guide services, improve service quality, support the growth of more organized local tourism, and support the transformation of tourism services in Indonesia.
Keywords: Transformasi Pariwisata; Tour Guide; Android; Extreme Programming (XP)